The Role of Overconfidence on Online Overdebt Behavior - Ascaryan Rafinda; Putri Purwaningtyas; Juli Riyanto Tri Wijaya; Hasan Aljafa; Christian Rotimi Barika; Annisa Ilma Hartikasari (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Purpose: The study aimed to examine the relationship between overconfidence bias and online overdebt behavior across four countries: Indonesia, Hungary, Poland, and Romania. Method: A total of 900 participants were surveyed, with 210–230 participants from each country, ensuring a diverse and heterogeneous sample in terms of age, gender, education level, and income. Data is processed using AMOS 24 software. Findings: The results from the SEM analysis supported all four hypotheses. Overconfidence bias is positively associated with online overdebt behavior, financial literacy moderates the relationship between overconfidence bias and online overdebt behavior, the ease of access to credit via online platforms amplifies the effect of overconfidence on online overdebt behavior, and overconfidence bias is associated with an underestimation of future financial risk in online borrowing. Implications: The significant role of digital credit access suggests that regulators must implement stricter controls on the 'ease-of-borrowing' features in fintech apps to prevent structural factors from amplifying cognitive biases in risky financial decision-making. Novelty/Value: The study’s novelty lies in its cross-continental analysis—spanning Indonesia, Hungary, Poland, and Romania—providing a rare look at relationships online debt behavior. Recent studies have shown that overconfidence can influence consumer decisions in debt markets, such as credit card usage and loans, potentially leading to dangerous overleveraging behaviors. The gap research is the limited study examining the specific mechanisms through which overconfidence influences online overdebt behavior.